An Innovative Approach to Pretest Questionnaire: The Analysis of Respondents' Comments in the Flexible Interview. (February 2020) - Palmieri, Marco
The researcher, who pretests a questionnaire conventionally, is confident that a small number of interviews reveals numerous problems afflict the questionnaire. The standardized interviewer is asked to observe respondent's verbal behaviors in order to realize whether respondent misunderstands question. But this strategy fails when respondent does not show any misunderstanding signal. The study, reported in this article, illustrates how to exceed this limit, by means of the analysis of respondent's comments released in the flexible interview, which researcher uses to unveil incongruities between question and answer; the questions, when many respondents' misunderstandings occur, should be reworded. This study shows that the number of problems and the number of the problematic questions identified by this unconventional procedure are much higher than the number of problems and the number of problematic questions determined by the conventional pretesting. The strength of respondents' comments analysis is to discover problems the questionnaire poses for respondents, even when the respondents do not give any misunderstanding signal.